IUS Constituendum of Suistainable Agricultural Policy: The Aftermath of Job Creation Act - Ruetaitip Chansrakaeo; Ermanto Fahamsyah (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
Agriculture is an important aspect of the life of the Indonesian people. Apart from being a commodity, agriculture is also a part of Indonesian people’s lives. In this case, the state needs to enact legal policies related to sustainable agriculture. This study seeks to discuss legal issues in the form of legal disharmony related to sustainable agricultural legal policies. This research is normative legal research. The study results confirm that the disharmony of legal policies related to Sustainable Agriculture has only become a “paper tiger,” which means that the rules exist but cannot be implemented because they do not have to implement regulations, so they are difficult to implement. That happens because the respective laws, particularly those related to sustainable agricultural cultivation systems and job creation, which substantially regulate sustainable agriculture, do not refer to each other. That impacts the lack of coordination and horizontal harmonization between fellow laws that substantially regulate sustainable agriculture. Harmonization is also not carried out vertically between Laws and Government Regulations. That occurs when Government Regulations relating to the administration of the agricultural sector do not refer to and harmonize vertically with the Law relating to sustainable agricultural cultivation systems. The results of this study also suggest that in the future, the government, in this case, needs to revise the Government Regulations relating to the implementation of the agricultural sector by incorporating the substance of the Sustainable Agriculture policy as well as being more thorough in harmonizing both vertically and horizontally in drafting legislation.